Milton Rojas M. y Gaitán Villavicencio. El proceso urbano de Guayaquil, 1870-1980. Guayaquil : ILDIS-CER-G, 1988. 254 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1989)
MILTON ROJAS M. y GAITÁN VILLAVICENCIO, El proceso urbano de Guayaquil 1870-1980, ILDIS-CER-G, Guayaquil, 1988.